The Chinese Ethnic Religious System in the Novel Kancing yang Terlepas by Handry TM - Setiyoningsih, Titi; Suwandi , Sarwiji; Wardani, Nugraheni Eko; Ulya, Chafit; Zulianto, Sugit (Lingua Cultura, 2023)
The research aimed to explain (1) the idea of a religious system, (2) the activities related to the religious system, and (3) cultural products related to the religious system in Handry TM’s novel on titled Kancing Yang Terlepas. The research applied a descriptive qualitative method with a content analysis strategy. The data of this research were words, phrases, clauses, sentences, paragraphs, and discourse in the novel. The data collection technique was a document analysis using the theory of literary anthropology. The data validity technique used theoretical triangulation through data validity activities based on various theoretical perspectives. The novelty of the research was that no one had previously analyzed the religious system in the novel before. The data analysis technique used interactive analysis. The results indicate that (1) the idea of the religious system represented in ‘Kancing yang Terlepas’ appears in the form of the idea of belief in supernatural beings and ideas in the form of ideas that contain procedures, Chinese New Year ritual rules, and death ceremonies; (2) the activities related to the religious system in ‘Kancing Yang Terlepas’ can be seen in the forms of Chinese New Year celebrations, mourning periods, and ancestor worship; (3) artifacts in the field of religion in ‘Kancing yang Terlepas’ are used as a complement in ethnic Chinese religious rituals, namely in the form of a statue of the Kitchen God, Huo or incense, a place for offerings, red paper for prayers, lanterns, and caskets. The religious system adhered to by the Chinese in the novel ‘Kancing Yang Terlepas’ still refers to the teachings of their ancestors from China.